2005
DOI: 10.1093/nar/gki851
|View full text |Cite
|
Sign up to set email alerts
|

Triplex targeted genomic crosslinks enter separable deletion and base substitution pathways

Abstract: We have synthesized triple helix forming oligonucleotides (TFOs) that target a psoralen (pso) interstrand crosslink to a specific chromosomal site in mammalian cells. Mutagenesis of the targeted crosslinks results in base substitutions and deletions. Identification of the gene products involved in mutation formation is important for developing practical applications of pso-TFOs, and may be informative about the metabolism of other interstrand crosslinks. We have studied mutagenesis of a pso-TFO genomic crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 74 publications
(108 reference statements)
7
44
0
Order By: Relevance
“…Our work in human cells corroborates and complements prior work, all in Chinese hamster ovary cells, demonstrating that ERCC1, which normally is in a heterodimeric complex with XPF, is required for the initial incisions and γ-H2AX formation [32], and that XPF and ERCC1 are required for incisions leading to DSB in an in vitro assay [14]. Our results are also consistent with the finding that XPF loss suppresses sister chromatid exchange following mitomycin C treatment [49], as well as with models in which the ICL-specific 5′ and 3′ endonuclease activities of the XPF-ERCC1 complex are a relatively early event preceding and required for DSB formation [25,32,50]. Although cell extracts have been reported to make dual incisions 5′ to a psoralen ICL, one of which was dependent on XPF, no DSB occurred as a result of this reaction, and thus these types of incisions alone do not explain the dependence of DSB formation on XPF [51].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our work in human cells corroborates and complements prior work, all in Chinese hamster ovary cells, demonstrating that ERCC1, which normally is in a heterodimeric complex with XPF, is required for the initial incisions and γ-H2AX formation [32], and that XPF and ERCC1 are required for incisions leading to DSB in an in vitro assay [14]. Our results are also consistent with the finding that XPF loss suppresses sister chromatid exchange following mitomycin C treatment [49], as well as with models in which the ICL-specific 5′ and 3′ endonuclease activities of the XPF-ERCC1 complex are a relatively early event preceding and required for DSB formation [25,32,50]. Although cell extracts have been reported to make dual incisions 5′ to a psoralen ICL, one of which was dependent on XPF, no DSB occurred as a result of this reaction, and thus these types of incisions alone do not explain the dependence of DSB formation on XPF [51].…”
Section: Discussionsupporting
confidence: 89%
“…Cisplatin forms a small number of ICL and fails to induce DSB in rodent cells [48]. NER processing of psoralen ICL that depends on XPA and other NER proteins to uncouple one strand of the ICL [21,22], followed by translesion synthesis with a bypass polymerase may be one scenario that could account for reduced DSB formation in GM637 cells relative to XP-A cells [11,20,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that polymerase ζ is the predominant determinant of ICL repair [14][15][16]. However, in yeast, REV3 activity in ICL repair was restricted exclusively to the G1 phase of the cell cycle, leaving open the possibility that other TLS polymerases might fulfill similar roles in other phases of the cell cycle [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that TLS by polymerase ζ plays a key role in repairing ICL [11,[14][15][16]. However, another polymerase involved in TLS, polymerase η (pol η), has also been variably implicated in ICL repair.…”
Section: Introductionmentioning
confidence: 99%
“…Further support for involvement of pol and another TLS polymerase, Rev1, in tolerance to ICL damage and their contribution to ICL-associated mutagenesis was obtained in both yeast (7,12) and vertebrate cells (6,8,13).…”
mentioning
confidence: 87%